EFEKTIVITAS DAN EFISIENSI PENGELOLAAN ALOKASI DANA DESA DI DESA AMESSANGANG KECAMATAN LANRISANG KABUPATEN PINRANG - Ahmad, NurIlmhy Pratiwi; Sulkarnain; Zainal Said; Darwis (Program Studi Manajemen Keuangan Syariah IAIN Parepare, 2025)
The effectiveness and efficiency of village fund allocation management can be known through the achievement of goals or objectives that have been set previously. Effectiveness and efficiency can be measured if there are results or achievements from various activities or projects that have been carried out. This study aims to determine the level of Effectiveness and Efficiency of Village Fund Allocation Management in Amassangang Village, Lanrisang District, Pinrang Regency. This research uses quantitative research and for data collection using observation and documentation methods and supporting data in the form of Village Fund Allocation (ADD) reports for the last 3 years from 2021-2023. The results showed that the Effectiveness and Efficiency of Village Fund Allocation Management in Amassangang Village, Lanrisang District, Pinrang Regency was considered effective, but inefficient. The effectiveness of the management of village fund allocations is considered effective and is evidenced by the average percentage value of effectiveness of 99.84%. Meanwhile, the efficiency of village fund allocation management is considered inefficient through the average percentage value of efficiency of 100.87%.